Analysis of the Efficiency of the Electrohydrodynamic Propulsion Based on the Biefeld-Brown Effect for Manned and Unmanned Aircrafts - Manés F. Cabanas; Francisco P. González; Andrés S. González; Moisés R. García; Manuel G. Melero (Applied Sciences, 2022)
The phenomenon known as the Biefeld-Brown effect or ionic wind has been the subject of study since its discovery with the aim of being applied to aircraft propulsion. Electrohydrodynamic (EHD) thrusters have been developed in a thorough and detailed way since 2000. Subsequently, some attempts have been made to extend them to electric-powered atmospheric aircrafts. This paper is framed in this field by performing a rigorous and detailed analysis of the energy efficiency, measured as the ratio of thrust to energy consumed, for both EHD systems and conventional electric propulsion. This is done using simple EHD thruster configurations together with accurate measurements of the current consumed under controlled environmental conditions. The results are not only compared with the performance of an electric propulsion motor-propeller set, but also consider future research, summarizing the issues that arise to scale them. Future designs of low weight, high performance thrusters might allow this technology to be applied to manned or remotely piloted aircrafts.